PENGEMBANGAN E–MODUL PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN CANVA MATERI SIKAP BANGGA SEBAGAI BANGSA INDONESIA DI KELAS IV SD - Wiwik Okta Susilawati; Antik Estika Hader; Aulia Tifani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study is motivated by problems in the implementation of the Pancasila Education learning process in class IV, namely the low interest in learning of students and the low learning outcomes of students. Efforts to overcome these problems are to develop learning e-modules that can improve student learning outcomes with complete videos, quizzes and attractive images. This type of research uses the type of research and development R & D (Research and Development). The development model used is the 4D development model, namely: Define, Design, Development and Disseminate. Define stage, at this stage curriculum analysis, needs analysis, analysis of learner characteristics, and technology analysis are carried out. Stage Design, the design stage is carried out the design of teaching modules, the design of the e-module framework for learning Pancasila Education grade IV, and the design of research instruments. Development stage, which is carried out validation test, practicality test, and effectiveness test. The Disseminate stage, at this stage, is the distribution of Pancasila Education learning e-module products which are limited to SDN 04 Koto Baru. The results of this research and development have produced teaching materials for e-modules for learning Pancasila Education using Canva material on proud attitudes as an Indonesian nation in class IV SDN 03 Koto Baru obtained from 8 validators, the validity of e-modules obtained from 5 validation experts gets an average percentage of 87.5% with a very valid category, the practicality of e-modules obtained from educators and small group students with an average percentage of 96.32% in the very practical category, the results of the effectiveness carried out by 27 students who took part in learning using the developed learning e-modules with an average of 92.59% so that the teaching materials for learning e-modules are very effective.